Material, and filter with material
A filter material with a zinc phosphate film and nanodiamond particles addresses the ineffectiveness of existing filters by providing robust antiviral protection against diverse viruses, especially non-enveloped types, through its unique structure and composition.
Patent Information
- Application Number
- JP2023115890
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
AI Technical Summary
Existing filters do not effectively inactivate a wide range of viruses, particularly non-enveloped viruses like norovirus, on dry surfaces, and there is a risk of residual infectious agents on the filter becoming a source of infection.
A material comprising a base material with a zinc phosphate film having micron-order unevenness and attached nanodiamond particles with a positive zeta potential, which is integrated into a filter to enhance antiviral efficacy.
The material exhibits excellent antiviral effects against various viruses, including non-enveloped viruses like feline calicivirus, with a logarithmic reduction value of 1.0 or more, ensuring reduced viral infectivity on dry surfaces.
Smart Images

Figure 2025012789000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a material and a filter with the material. More specifically, the present disclosure relates to a material and a filter with the material that has a bacteria and virus removal effect and an antibacterial and antiviral effect. [Background technology]
[0002] Many viral diseases caused by novel coronaviruses, influenza viruses, noroviruses, etc. are transmitted through various routes of infection, such as droplet infection, droplet nuclei infection, and contact infection. Among these, droplet nuclei infection is a route of infection in which very fine particles emitted by a patient remain suspended in the air for a long time, and people in the same space as the patient inhale the virus, which can cause the infection to spread, especially in small, enclosed spaces.
[0003] Incidentally, the new coronavirus and influenza virus are enveloped viruses with lipid membranes, and have relatively low resistance, for example, disinfection with lipid-soluble ethanol is effective. On the other hand, norovirus is a non-enveloped virus that does not have an envelope, so ethanol disinfection alone is not effective against them, and they are known to be highly resistant, for example, they are resistant to drying and heating.
[0004] Furthermore, norovirus is so contagious that infection can occur with fewer than 100 virus particles, and it is known that droplet nucleus infection can occur when tiny amounts of vomit or feces from an infected person are dispersed into the air.
[0005] Conventionally, preventive measures against droplet nuclei infection have been implemented by capturing and removing airborne bacteria and viruses using filters. However, simply capturing bacteria and viruses on the filter has the problem that the bacteria and viruses remain infectious and the filter itself can become a source of infection.
[0006] In order to overcome the above problems, filters that have antibacterial or antiviral effects against captured bacteria or viruses, or materials that can be attached to or detached from filters, are known.
[0007] Patent Document 1 discloses that by performing a zinc phosphate conversion treatment on the surface of a metal substrate and forming a zinc phosphate film having micron-order irregularities on the surface, the zinc phosphate film exhibits antifungal, bactericidal, and antiviral effects.
[0008] Nanodiamond particles are ultrafine diamond particles with an extremely large specific surface area, and due to their properties they are also used as antibacterial and antiviral ingredients.
[0009] Patent document 2 discloses that when a dispersion liquid containing nanodiamond particles is mixed with a solution containing influenza viruses, the dispersion liquid containing the nanodiamond particles exhibits the effect of inactivating the influenza viruses.
[0010] Patent Document 3 discloses that applying a nonwoven fabric sheet impregnated with a coating liquid containing silver particles, diamond particles, ethanol, and water to a wall and / or a ceiling can impart antiviral properties. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] International Publication No. 2021 / 193843 [Patent Document 2] Patent Publication No. 2022-161727 [Patent Document 3] JP 2023-7158 A Summary of the Invention [Problem to be solved by the invention]
[0012] However, the material described in Patent Document 1 discloses an antiviral effect against bacteriophage Qβ under wet conditions (in a liquid phase), but does not disclose its effect against other viruses or its effect on a dry surface (in a gas phase), which is the expected condition under which the filter will actually be used, and there is room for further study.
[0013] Furthermore, the dispersion liquid containing nanodiamond particles described in Patent Document 2 discloses an antiviral effect against influenza viruses under wet conditions (in the liquid phase), but does not disclose its effect against other viruses or its effect on dry surfaces (in the gas phase), which is the expected condition under which the filter will actually be used, leaving room for further study.
[0014] Furthermore, the antiviral nonwoven fabric sheet described in Patent Document 3 does not disclose its specific effectiveness against viruses other than the new coronavirus, nor its effectiveness on dry surfaces (in the gas phase), which is the assumed condition under which the filter will actually be used.
[0015] Therefore, an object of the present disclosure is to provide a material and a filter with the material that exhibits excellent antiviral effects against various viruses. [Means for solving the problem]
[0016] As a result of intensive research to achieve the above object, the inventors of the present disclosure have found that the above material exhibits excellent antiviral effects against various viruses by having a main body having an uneven surface and nanodiamond particles attached to the uneven surface. The present disclosure has been completed based on these findings.
[0017] That is, the present disclosure provides a material comprising a main body having an uneven surface and nanodiamond particles adhered to the uneven surface.
[0018] The main body preferably includes a substrate and a coating formed on the substrate.
[0019] The coating is preferably a zinc phosphate coating.
[0020] The zeta potential of the nanodiamond particles is preferably positive.
[0021] The present disclosure also provides a filter with the material, in which the material is attached to a filter body.
[0022] The present disclosure also provides a nanodiamond particle dispersion for use in preparing the above material.
[0023] The present disclosure also provides at least one product selected from the group consisting of a coating liquid, a plating liquid, and a chemical conversion treatment liquid, which contains the nanodiamond particle dispersion liquid used in producing the material. Effect of the Invention
[0024] The material of the present disclosure has the above-mentioned configuration and is therefore capable of exhibiting antiviral effects against various viruses. In addition, the present disclosure can provide a material-attached filter in which the material is assembled into a filter. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a schematic diagram of a material-containing filter according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is an enlarged schematic diagram of a material according to an embodiment of the present disclosure. [Diagram 3] 11A and 11B are diagrams for explaining a procedure for calculating the interval between adjacent convex portions. [Figure 4] 1 is a schematic diagram of a process for preparing a material according to an embodiment of the present disclosure. [Diagram 5] 1 is a scanning electron microscope photograph of the material produced in Comparative Example 1. [Figure 6] 1 is a scanning electron microscope photograph of the material prepared in Example 1. [Figure 7] 1 is a scanning electron microscope photograph of the material prepared in Example 2. [Figure 8] 1 is a scanning electron microscope photograph of the material produced in Example 3. [Figure 9] 1 is a scanning electron microscope photograph of the material produced in Example 4. [Figure 10] 1 is a scanning electron microscope photograph of the material produced in Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] In this specification, a filter having the above-mentioned material attached thereto may be referred to as a "filter with material". In addition, in this specification, the effect evaluated by the "virus suppression performance evaluation test" described below, which refers to the Japan Electrical Manufacturers' Association standard JEM1467 "Household air purifiers" Annex F "Test method for evaluating the suppression performance against viruses captured by a filter", may be referred to as the "antiviral effect".
[0027] [Materials and filters with materials] The material according to one embodiment of the present disclosure has a configuration including a main body having an uneven surface and nanodiamond particles attached to the uneven surface.
[0028] Hereinafter, an embodiment of the material and the material-containing filter of the present disclosure will be described with reference to the drawings, but the material and the material-containing filter of the present disclosure are not limited to this embodiment. Fig. 1 is a schematic diagram showing an embodiment of the material-containing filter of the present disclosure.
[0029] 1, the material-attached filter 1 includes a rectangular box-shaped filter body 2 and a mesh-like material 3 attached to the filter body 2 so as to cover at least a portion of the filter body 2. In the present embodiment, the material 3 is attached to the filter body 2 so as to cover one entire surface of the filter body 2, but the present disclosure is not limited to this. It is sufficient that at least a portion of the filter body 2 is covered by the material 3. The filter body is not particularly limited, and a publicly known or commonly used filter can be used.
[0030] The material 3 includes a rectangular purification section 30 that is substantially the same shape as the filter body 2 in a plan view, and a band-like first leg section 31 and a band-like second leg section 32 that extend along opposing long sides of the four sides of the purification section 30. By including such legs, the material 3 is held by the filter body 2 and can be used as a single unit.
[0031] FIG. 2 is an enlarged schematic diagram of one embodiment of the material 3. The material 3 includes a main body 4 and nanodiamond particles 5. The main body 4 is composed of a substrate 41 and a coating 42. The substrate 41 is, for example, a mesh-shaped metal substrate, more specifically, an aluminum alloy mesh substrate containing A5056. A coating 42 is formed on the surface of the substrate 41, and more specifically, a zinc phosphate coating having fine irregularities is formed by a zinc phosphate chemical conversion treatment described later, resulting in an irregular shape being formed on the surface of the main body 4. Furthermore, nanodiamond particles 5 are attached to the surface of the coating 42 (the irregular surface of the main body 4) by a nanodiamond particle attachment treatment described later. Below, a case where the aluminum alloy mesh substrate is used as the substrate 41 and the zinc phosphate coating is used as the coating 42 will be described, but the present disclosure is not limited thereto.
[0032] (Main body) The main body preferably has at least a substrate. More preferably, the main body has the substrate and a coating formed on the substrate. The substrate and the coating may each be a single layer, or two or more layers may be laminated.
[0033] The substrate is not particularly limited, and known or conventional metal substrates or resin substrates can be used. Metal substrates include, for example, substrates made of aluminum, aluminum alloys containing aluminum as the main component and copper, manganese, silicon, magnesium, zinc, and nickel, iron, stainless steel, magnesium, magnesium alloys, titanium, titanium alloys, copper, copper alloys, nickel, nickel alloys, chromium, and chromium alloys. Resin substrates include, for example, substrates made of polyolefin resins, polyolefin copolymer resins, polyester resins, acrylic resins, polyamide resins, polyimide resins, polycarbonate resins, phenolic resins, epoxy resins, silicon resins, styrene resins, fluorine resins, and urethane resins. The material constituting the substrate may be one type only, or two or more types may be used.
[0034] From the viewpoints of durability and processability, the substrate is preferably a metal substrate. Among them, from the viewpoints of light weight and processability, a substrate made of aluminum or an aluminum alloy is more preferable, and a substrate made of an aluminum alloy is even more preferable.
[0035] The shape of the substrate is not particularly limited, and may be, for example, a mesh, a flat plate, a nonwoven fabric, etc. Among these, a mesh is preferred from the viewpoint of not impairing the function of the filter body when assembled into the filter body.
[0036] The main body has an uneven surface, but the surface of the base material may be smooth or uneven. When the base material has an uneven surface, the unevenness may form the unevenness of the main body surface.
[0037] The thickness of the substrate is not particularly limited, and can be selected from thicknesses of, for example, 0.1 μm or more.
[0038] The coating has the ability to impart functions to the main body, such as antiviral, bactericidal, and antifungal effects, and the effect of adhering nanodiamond particles.
[0039] The coating is not particularly limited, and known or conventional coatings can be used. For example, phosphate coatings such as zinc phosphate coating, manganese phosphate coating, iron phosphate coating, and calcium phosphate coating can be mentioned. Among them, zinc phosphate coating is preferred from the viewpoints of excellent antiviral effect, easy adjustment of the size of unevenness, and easy attachment of nanodiamond particles. In addition, the coating may be provided on the substrate via another coating such as a zinc coating in order to improve adhesion to the substrate.
[0040] The thickness of the coating is not particularly limited and can be selected from thicknesses of, for example, 0.1 μm or more.
[0041] The main body has an uneven surface. The uneven surface may be on the surface of the substrate, or may be on the coating. When the substrate surface has an uneven surface, the coating may be formed along the uneven surface so as to maintain the uneven surface of the substrate. The main body 4 in FIG. 2 has a coating 42 having an uneven surface formed on the flat surface of a substrate 41.
[0042] The interval between the projections in the unevenness of the main body is preferably 0.5 to 50.0 μm, more preferably 0.5 to 6.0 μm, from the viewpoints of excellent antiviral effect, easy adjustment of the size of the unevenness, and easy attachment of nanodiamond particles. The interval between the projections can be calculated by the procedure described below.
[0043] Fig. 3 is a diagram for explaining a procedure for calculating the interval between adjacent protrusions. As shown in Fig. 3, countless blade-like protrusions 42a (parts that appear bright in Fig. 3) with irregular orientations are formed on the surface of the zinc phosphate coating 42. Therefore, countless recesses 42b (parts that appear dark in Fig. 3) are formed on the surface of the zinc phosphate coating 42 as concave spaces partitioned by the countless protrusions 42a.
[0044] In this specification, the length of one side of the recess 42b in plan view is defined as the interval between adjacent protrusions 42a in plan view. More specifically, the shape of each recess 42b formed on the surface of the zinc phosphate coating 42 in plan view is considered to be a shape (e.g., rectangular or elliptical) that can define the longitudinal direction LD and the transverse direction SD perpendicular thereto, and the longitudinal direction LD and the transverse direction SD perpendicular thereto are defined for each recess 42b, and the length of the recess 42b along the longitudinal direction LD and the transverse direction SD is defined as the interval between adjacent protrusions 42a. Based on the above definition, the length of each recess 42b along the longitudinal direction LD and the transverse direction SD is calculated, and the minimum value of the length along the transverse direction SD is defined as the minimum value of the interval between the protrusions 42a, and the maximum value of the length along the longitudinal direction LD is defined as the maximum value of the interval between the protrusions 42a.
[0045] The thickness of the main body is not particularly limited and can be selected from a range of thicknesses, for example, 0.1 μm or more. From the viewpoint of stably forming the uneven shape, the thickness is preferably 0.1 μm or more, more preferably 0.25 μm or more, and even more preferably 0.5 μm or more.
[0046] (Nanodiamond particles) In this specification, "nanodiamond particles" refers to diamond particles whose primary particle size (average primary particle diameter) is less than 1000 nm. The average primary particle diameter of the nanodiamond particles is, for example, 100 nm or less, preferably 60 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. The lower limit of the average primary particle diameter of the nanodiamond particles is, for example, 1 nm.
[0047] The nanodiamond particles are not particularly limited, and known or conventional nanodiamond particles can be used. The nanodiamond particles may be surface-modified or non-surface-modified. The non-surface-modified nanodiamond particles have many hydroxyl groups (-OH) and carboxyl groups (-COOH) on the surface. The nanodiamond particles may be one type or two or more types.
[0048] In the above-mentioned surface-modified nanodiamond particles, the compound or functional group that modifies the surface of the nanodiamond particles is not particularly limited, and examples thereof include a hydrogen group (CH group), a silane compound, a phosphonate ion or a phosphonate residue, a surface-modifying group having a vinyl group at the end, an amide group, a cation of a cationic surfactant, a group containing a polyglycerin chain, and a group containing a polyethylene glycol chain.
[0049] From the viewpoint of antiviral effect, it is preferable that the above-mentioned nanodiamond particles have at least hydrogen groups, hydroxyl groups, or carboxyl groups on the surface.
[0050] The zeta potential of the nanodiamond particles may be negative or positive. Nanodiamond particles having many hydroxyl groups or carboxyl groups on the surface, such as nanodiamond particles that are not surface-modified, tend to have a negative zeta potential due to oxygen-based functional groups. On the other hand, nanodiamond particles having many hydrogen groups on the surface, such as by reduction treatment such as hydrogenation, tend to have a positive zeta potential due to surface termination with hydrogen. Among them, the zeta potential of the nanodiamond particles is preferably positive. By using nanodiamond particles with a positive zeta potential, the antiviral effect tends to be sufficient against a wide range of viruses.
[0051] In this specification, the zeta potential of the nanodiamond particles is negative, and the zeta potential of the nanodiamond particles is negative when the dispersion medium has a pH of 5 to 9 and an ionic strength of 1.0×10 at 25° C., as measured by, for example, laser Doppler electrophoresis. -4 This means that the value of the zeta potential at M is a negative value. The zeta potential is, for example, −80 to −5 mV, preferably −70 to −10 mV, and more preferably −60 to −20 mV.
[0052] In this specification, the zeta potential of the nanodiamond particles is positive, and the positive potential is determined by, for example, a laser Doppler electrophoresis method, and the pH of the dispersion medium is 5 to 9 and the ionic strength is 1.0 × 10 at 25 ° C. -4 This means that the value of the zeta potential at M is a positive value. The zeta potential is, for example, 5 to 80 mV, preferably 10 to 70 mV, and more preferably 20 to 60 mV.
[0053] The average primary particle diameter (D50) of the nanodiamond particles is, for example, 100 nm or less, preferably 60 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. The lower limit of the average primary particle diameter of the nanodiamond particles is, for example, 1 nm. If the primary particle diameter is 100 nm or less, the nanodiamond particles can be more densely attached to the coating surface. The average primary particle diameter can be measured by image analysis (TEM, SEM, etc., electron microscope measurement) in a powder state or by X-ray diffraction. In the case of electron microscope measurement, the particle diameter corresponding to 50% of the particle diameter from the small particle diameter side in the particle size distribution (number basis) of the circle equivalent diameter based on electron microscope observation can be the average primary particle diameter. In addition, when the nanodiamond particles are approximately spherical, the average value of the longest diameter may be the average primary particle diameter.
[0054] The nanodiamond particles may be attached to the surface of the main body in a dispersed state, or in a state of secondary particles (aggregates) in which a plurality of primary particles are aggregated. The size of the secondary particles is about 10 to 200 times the average particle size of the primary particles. For example, it is 50 to 1000 nm, preferably 50 to 500 nm, more preferably 50 to 200 nm, and even more preferably 50 to 100 nm. When the secondary particle diameter is within the above range, the secondary particles are less likely to precipitate in the nanodiamond particle attachment process described later, and therefore can be attached uniformly to the coating surface. The attachment mode can be observed by image analysis (electron microscope measurement such as TEM and SEM).
[0055] The coating amount (A) of the nanodiamond particles per surface area of the material is preferably 0.02 mg / cm 2 More preferably, it is 0.05 mg / cm or more. 2 More preferably, it is 0.1 mg / cm 2 More preferably, it is 0.2 mg / cm or more. 2 The amount of nanodiamond particles applied per surface area of the material (A) is preferably 1 mg / cm 2 More preferably, it is 0.7 mg / cm or less. 2 or less, more preferably 0.5 mg / cm 2 or less, and particularly preferably 0.4 mg / cm 2 Here, the coating amount (A) is calculated by the procedure described below. The coating amount can be adjusted by changing the concentration of nanodiamond particles in the nanodiamond particle dispersion liquid or the solvent of the dispersion liquid in the nanodiamond particle attachment process described below.
[0056] As the above-mentioned nanodiamond particles, for example, detonation nanodiamond (i.e., nanodiamond produced by detonation), high-temperature high-pressure nanodiamond (i.e., bulk diamond produced by high-temperature high-pressure method is crushed to nanoparticles), or chemical vapor deposition nanodiamond (i.e., thin film diamond obtained by chemical vapor deposition method is crushed to nanoparticles) can be used. Among them, detonation nanodiamond is preferred because the particle diameter of the primary particle is one digit nanometer.
[0057] The detonation nanodiamond includes air-cooled detonation nanodiamond (i.e., nanodiamond produced by air-cooled detonation) and water-cooled detonation nanodiamond (i.e., nanodiamond produced by water-cooled detonation). Among them, air-cooled detonation nanodiamond is preferable because it has smaller primary particles than water-cooled detonation nanodiamond. The nanodiamond particles may be primary particles of nanodiamond, or may be secondary particles formed by agglomeration (adhesion) of multiple primary particles.
[0058] In embodiments of the material of the present disclosure, the material may be assembled into a known or conventional filter body to form a material-attached filter. Such material-attached filters may be used in automotive air conditioners, air conditioners, air purifiers, and the like.
[0059] In the embodiment of the material of the present disclosure, the use conditions of the material-attached filter are not particularly limited, and the material-attached filter can be used under any of the conditions of gas phase, liquid phase, and solid phase, for example. Among them, the material is preferably used in the gas phase from the viewpoint that the effect of the material is easily exhibited. The state of each of the above phases is not particularly limited. For example, in the gas phase, the type of gas, temperature, humidity, and pressure are not limited, but when used in the above-mentioned automotive air conditioner, air conditioner, air purifier, etc., the material-attached filter can be used in air at normal temperature and normal pressure.
[0060] The material of the present disclosure has a main body having micron-order irregularities and nanodiamond particles, and thus exhibits an antiviral effect against various viruses. Examples of viruses include enveloped and non-enveloped viruses. Among them, the material has an excellent antiviral effect against non-enveloped viruses, and is particularly excellent in antiviral effect against feline calicivirus. From the viewpoint of infection prevention measures, a logarithmic reduction value of 1.0 or more is preferable, and a logarithmic reduction value of 2.0 or more is more preferable, in the test method for evaluating the suppression performance against feline calicivirus described later.
[0061] It is believed that micron-order irregularities exert a bactericidal effect due to a physical action derived from the shape (for example, the cell wall itself is deformed and killed when bacteria pierce the irregularities). On the other hand, for example, influenza viruses are 80 to 120 nm in size, and feline caliciviruses are 27 to 35 nm in size, which is about one-tenth the size of general bacteria (0.5 to 2 μm). Therefore, viruses are unlikely to pierce micron-order irregularities, and it is possible that the antiviral effect is difficult to exert. Therefore, the material of the present disclosure is believed to be able to exert a composite effect derived from the irregular shape and the nanodiamond particles, such as the nanodiamond particles acting on viruses that have entered the concaves of the irregularities by stably attaching a large number of nanodiamond particles using the large specific surface area due to the irregularities. Therefore, it is believed that the material of the present disclosure, having the above-mentioned configuration, can exhibit excellent antibacterial and antiviral effects against microorganisms of various sizes.
[0062] In the embodiment of the material of the present disclosure, a material having at least one of the effects of antiviral effect, antibacterial effect, and antifungal effect may be specifically referred to as a "functional material". Here, the definition of each effect may refer to the general definition in the art. "Antiviral effect" means an effect evaluated, for example, by ISO 21702:2019 Measurement of antiviral activity on plastics and other non-porous surfaces, etc. "Antibacterial effect" means an effect evaluated, for example, by JIS Z 2801:2012 "Antibacterial processed products - Antibacterial test method, antibacterial effect" etc. "Anti-fungal effect" means an effect evaluated, for example, by JIS Z 2911:2018 "Mold resistance test method" etc.
[0063] [Material manufacturing method] The above material can be produced by attaching nanodiamond particles to the main body by a known or conventional method. The above material can be produced, for example, by applying a nanodiamond particle dispersion to the main body and drying the nanodiamond particles to the main body. When the main body has the substrate and the coating, the substrate is treated to form a coating having fine irregularities on the metal surface, and then the nanodiamond particles can be attached by applying a nanodiamond particle dispersion and drying the coating.
[0064] Hereinafter, a method for manufacturing the material 3 shown in FIG. 2 will be described as an example. FIG. 4 is a schematic diagram of the manufacturing process of one embodiment of the material 3. As shown in FIG. 4, the material 3 can be manufactured, for example, by performing a cleaning process, a surface adjustment process, a zinc phosphate conversion treatment, and a nanodiamond particle attachment process on the substrate 41. More specifically, the process includes a process of cleaning, degreasing, and rinsing the substrate 41 (for example, an aluminum alloy mesh substrate) processed into a shape that can be assembled to the filter body, a surface adjustment process of immersing the substrate 41 in a surface adjustment liquid and attaching nuclei that will trigger crystallization to the surface, a process of forming a film 42, which is a zinc phosphate film having micron-order irregularities on the surface of the substrate 41, by performing a zinc phosphate conversion treatment in which the substrate 41 is contacted with a zinc phosphate treatment liquid for a predetermined time, and a process of attaching a plurality of nanodiamond particles 5 to the surface of the film 42 by immersing the substrate 41 in a nanodiamond particle dispersion liquid for a predetermined time and then drying the substrate.
[0065] 4 shows the case of zinc phosphate chemical conversion treatment, but the present disclosure is not limited thereto. For example, other phosphate conversion treatments (manganese phosphate chemical conversion treatment, iron phosphate chemical conversion treatment, calcium phosphate chemical conversion treatment), chemical conversion treatments such as boehmite treatment, chromate treatment, zincate treatment, etc., and surface treatments such as plasma treatment, blast treatment, etc. may be used. Among these, zinc phosphate chemical conversion treatment is preferred from the viewpoint of ease of adjusting the size of the unevenness.
[0066] In this specification, micron-order irregularities refer to a state in which the spacing between adjacent protrusions, calculated by the procedure described in FIG. 3, is within the range of 0.1 to 1000 μm, and an infinite number of such irregularities are formed by such protrusions.
[0067] (Surface conditioning process) The surface conditioning step is not particularly limited, and a known or conventional surface conditioning liquid can be used. For example, "PL-X" and "PL-XG" manufactured by Nihon Parkerizing Co., Ltd., adjusted to a predetermined concentration [g / L], can be used. By changing the concentration of the surface conditioning liquid, it is possible to change the unevenness formed on the surface of the metal substrate to a rough one or a fine one. The higher the concentration of the surface conditioning liquid, the finer the unevenness tends to be. From the viewpoint of forming unevenness on the order of microns, the concentration of the surface conditioning liquid is preferably 0.1 g / L or more, more preferably 1.0 g / L or more, and even more preferably 2.0 g / L or more. From the viewpoint of cost-effectiveness, the concentration of the surface conditioning liquid is preferably 10 g / L or less, more preferably 5.0 g / L or less.
[0068] (Zinc phosphate conversion coating) The zinc phosphate conversion treatment is not particularly limited, and any known or commonly used zinc phosphate treatment solution can be used, such as "PB-LA37", "Palbond 880", or "Ferricote 7" manufactured by Nihon Parkerizing Co., Ltd.
[0069] (Nano diamond particle attachment treatment) The nanodiamond particle dispersion liquid used in the nanodiamond particle attachment process contains nanodiamond particles and a solvent. The concentration of nanodiamond particles in the nanodiamond particle dispersion liquid is preferably 0.01 to 10 mass%, more preferably 0.05 to 5 mass%, and even more preferably 0.1 to 2 mass%. When the concentration of nanodiamond particles in the nanodiamond particle dispersion liquid is 0.01 mass% or more, the amount of attached nanodiamond particles is sufficient, and the antiviral effect is easily obtained.
[0070] The solvent of the nanodiamond particle dispersion liquid may be water, ethanol, methanol, isopropanol, isobutyl alcohol, ethylene glycol, propylene glycol, glycerin, 2-methoxyethanol, dimethylsulfoxide, N-methyl-2-pyrrolidone, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N,N-diethylacetamide, N,N-dimethylmethoxyacetamide, hexamethylphosphoramide, dimethylsulfone, propylene carbonate, etc. These solvents may be used alone or in combination of two or more. From the viewpoints of safety, handling, dispersibility, etc., it is preferable to contain at least water, and a mixed solvent of water and ethanol is more preferable.
[0071] The nanodiamond particle dispersion may be included in various products. Examples include coating liquids, plating liquids, and chemical conversion treatment liquids. The concentration of nanodiamond particles included in the above products is 0.01 to 10% by mass, preferably 0.05 to 5% by mass, and more preferably 0.1 to 2% by mass. When the concentration of nanodiamond particles in the nanodiamond particle dispersion is 0.01% by mass or more, the amount of nanodiamond particles attached is sufficient, and the antiviral effect is easily obtained.
[0072] In the above-mentioned nanodiamond particle attachment process, the method (coating method) for attaching nanodiamond particles is not particularly limited, and any known or commonly used coating method can be used. For example, dip coating method, spray coating method, roller coating method, slit coating method, spin coating method, etc. can be mentioned. Among them, dip coating method is preferred from the viewpoint of good attachment efficiency.
[0073] In the above-mentioned nanodiamond particle attachment process, the drying method is not particularly limited, and known or conventional drying methods can be used. For example, natural drying, vacuum drying, drying under a specific gas environment (the type of gas is not particularly limited, for example, argon, nitrogen, etc.), air blowing, heat drying, etc. can be mentioned. Since the purpose is to dry the solvent, natural drying is sufficient, but heat drying at about 100 ° C. may also be used depending on the heat resistance of the substrate.
[0074] Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. Each configuration in each embodiment and their combinations are merely examples, and addition, omission, substitution, and other modifications of the configuration are possible as appropriate within the scope of the present disclosure. In addition, each invention according to this disclosure is not limited by the embodiments or the following examples, but is limited only by the claims. EXAMPLES
[0075] Hereinafter, one embodiment of the present disclosure will be described in more detail based on examples.
[0076] Comparative Example 1 (Material preparation method) A material was produced by subjecting an aluminum alloy mesh substrate containing A5056 to the process shown in the schematic diagram of Figure 4. More specifically, an aluminum alloy mesh substrate with a wire diameter of 0.25 μm, a mesh hole diameter of 0.596 μm, and a pitch of 0.8467 μm was washed, and then subjected to a surface conditioning process in which the substrate was immersed in a surface conditioning solution with a concentration of 3 g / L, and a zinc phosphate conversion treatment in which the substrate was immersed in a zinc phosphate treatment solution "PB-LA37" to produce the material.
[0077] Example 1 The material prepared in Comparative Example 1 was subjected to the following steps to prepare a material.
[0078] (Preparation process of nanodiamond particle dispersion) 103.4 g of ζ(+) nanodiamond raw material solution (product name "Dinobear", manufactured by Daicel Corporation, nanodiamond particle concentration in the raw material solution: 2.91% by mass, zeta potential at pH 3.0: +40 mV) was weighed into a container, 1.9 g of water and 45.0 g of ethanol were added as solvents, and the mixture was stirred at room temperature to prepare 150 g of nanodiamond particle dispersion liquid in which the nanodiamond particles were uniformly dispersed. At this time, the nanodiamond particle concentration in the nanodiamond particle dispersion liquid was 2.0% by mass.
[0079] (Nano diamond particle attachment treatment) 150 g of the obtained nanodiamond particle dispersion was placed into a flat-bottomed metal container, and one sheet of material prepared by the procedure of Comparative Example 1 was impregnated therein, dipped in for 10 seconds, removed from the nanodiamond particle dispersion, tilted in the air and left to stand for 30 seconds, excess dispersion liquid was removed, and the material was then air-dried at room temperature for 3 hours to produce a material with nanodiamond particles attached.
[0080] Examples 2 to 5 Materials with nanodiamond particles attached were produced in the same manner as in Example 1, except that the nanodiamond particle dispersion liquid shown in Table 1 was used. In Examples 4 to 5, ζ(-) nanodiamond raw material liquid (product name "Dinobear", manufactured by Daicel Corporation, nanodiamond particle concentration contained in the raw material liquid: 5.68%, zeta potential at pH 9.0: -35 mV) was used as the nanodiamond raw material liquid. Note that the numerical values of the composition of the nanodiamond particle dispersion liquid in Table 1 refer to "g".
[0081] The surface state of the above-mentioned material produced by the above-mentioned process was observed by the "Surface state observation method" described below, and the results are shown in Figures 5 to 10. Note that all are backscattered electron images at 20,000 times magnification. In Figure 5 of Comparative Example 1, it was confirmed that a zinc phosphate coating having micron-order irregularities was formed, and in Figures 6 to 10 of Examples 1 to 5, it was confirmed that nanodiamond particles were further attached to the irregularities of the zinc phosphate coating.
[0082] The above material produced by the above process was evaluated in the "Virus Inhibitory Performance Evaluation Test" described below, and the results are shown in Table 1.
[0083] [evaluation] (Test to evaluate virus suppression performance) In order to evaluate the antiviral effect against viruses captured on the surface of the material, tests were conducted under the following conditions, referring to the Japan Electrical Manufacturers' Association standard JEM1467 "Household air purifiers" Annex F "Test method for evaluating the suppression performance against viruses captured on filters." In each test, the following materials were used as test or control items.
[0084] Test sample: a piece (5 x 5 cm) of the material of each Example or Comparative Example 1 Control: Glass plate (5 x 5 cm)
[0085] The viruses used were influenza A virus, which is designated as an indicator virus in the above-mentioned "Test method for evaluating the performance of suppressing viruses captured by a filter," E. coli phage, and feline calicivirus, which is known as an alternative to norovirus. Since norovirus, which infects humans, is difficult to culture and a method for experimental evaluation has not yet been established, feline calicivirus, which is structurally similar to norovirus and closely related to it, was used.
[0086] (Test method for evaluating inhibitory performance against influenza A virus) The following viruses and host cells were used: Influenza A virus, H1N1, A / PR / 8 / 34 (ATCC VR-1469) ·Host cells: MDCK cells (canine kidney cells) (ATCC CCL-34) (1) 0.1 mL of influenza A virus liquid was dropped onto the control product. (2) The control sample (1) was immediately washed with MEM (Minimum Essential Medium), PBS (phosphate buffered saline), or sterile ion-exchanged water to recover the virus on the control sample. The solution obtained by this process was used as the 0-second virus solution of the control sample. (3) The control product (2) was left in the test chamber for 24 hours, after which the control product was washed out with MEM, PBS, or sterile ion-exchanged water to recover the virus on the control product. The solution obtained by this process was used as the 24-hour virus solution of the control product. (4) 0.1 mL of influenza A virus fluid was dropped onto the test sample of each Example and Comparative Example. (5) The test sample (4) was left in the test chamber for 24 hours, after which it was washed out with MEM, PBS, or sterile ion-exchanged water to recover the virus on the control sample. The solution obtained by this process was used as the 24-hour virus solution of the test sample. (6) The collected control product 0-second active virus solution, control product 24-hour active virus solution, and test product 24-hour active virus solution were used as sample stock solutions to prepare 10-fold serial dilutions using MEM, PBS, or sterile ion-exchanged water. (7) 100 μL of the sample stock solution or diluted solution and 100 μL of MDCK cells suspended in MDCK cell medium were inoculated into a 96-well plate. (8)(7) was cultured in a carbon dioxide incubator, and the cytopathogenic effect (CPE) was confirmed under a microscope. The influenza A virus infectivity titer per mL of the washout solution was calculated using the Reed-Muench method.
[0087] (Test method for evaluating the inhibitory effect against feline calicivirus) The following viruses and host cells were used: Feline calicivirus, F-9 (ATCC VR-782) ·Host cell: CRFK cell (feline kidney-derived cell line) (ATCC CCL-94) (1) 0.1 mL of feline calicivirus liquid was dropped onto the control product. (2) The control sample (1) was immediately washed with MEM, PBS, or sterile ion-exchanged water to recover the virus on the control sample. The solution obtained by this process was used as the 0-second virus solution of the control sample. (3) The control product (2) was left in the test chamber for 24 hours, after which the control product was washed out with MEM, PBS, or sterile ion-exchanged water to recover the virus on the control product. The solution obtained by this process was used as the 24-hour virus solution of the control product. (4) 0.1 mL of feline calicivirus liquid was dropped onto the test sample of each of the Examples and Comparative Examples. (5) The test sample (4) was left in the test chamber for 24 hours, after which it was washed out with MEM, PBS, or sterile ion-exchanged water to recover the virus on the control sample. The solution obtained by this process was used as the 24-hour virus solution of the test sample. (6) The collected control product 0-second active virus solution, control product 24-hour active virus solution, and test product 24-hour active virus solution were used as sample stock solutions to prepare 10-fold serial dilutions using MEM, PBS, or sterile ion-exchanged water. (7) 100 μL of the sample stock solution or diluted solution and 100 μL of CRFK cells suspended in CRFK cell medium were inoculated into a 96-well plate. (8)(7) was cultured in a carbon dioxide incubator, and the cytopathogenic effect (CPE) was confirmed under a microscope, and the feline calicivirus infectivity titer per 1 mL of the washout solution was calculated using the Reed-Muench method.
[0088] (Test for evaluating the virus suppression performance against E. coli phages) The following viruses and host bacteria were used: ·Escherichia coli phage MS2(NBRC 102619) ·Host bacteria: Escherichia coli (NBRC 3012) (1) 0.1 mL of E. coli phage liquid was dropped onto the control product. (2) The control sample (1) was immediately washed with MEM, PBS, or sterile ion-exchanged water to recover the virus on the control sample. The solution obtained by this process was used as the 0-second virus solution of the control sample. (3) The control product (2) was left in the test chamber for 24 hours, after which the control product was washed out with MEM, PBS, or sterile ion-exchanged water to recover the virus on the control product. The solution obtained by this process was used as the 24-hour virus solution of the control product. (4) 0.1 mL of E. coli phage liquid was dropped onto the test samples of each of the Examples and Comparative Examples. (5) The test sample (4) was left in the test chamber for 24 hours, after which it was washed out with MEM, PBS, or sterile ion-exchanged water to recover the virus on the control sample. The solution obtained by this process was used as the 24-hour virus solution of the test sample. (6) The collected control product 0-second active virus solution, control product 24-hour active virus solution, and test product 24-hour active virus solution were used as sample stock solutions to prepare 10-fold serial dilutions using MEM, PBS, or sterile ion-exchanged water. (7) The sample undiluted solution or diluted solution was mixed with E. coli liquid medium in which E. coli had been cultured, and the mixture was allowed to stand at 35±1°C for 10 to 20 minutes. (8) The solution (7) was mixed with soft NB agar medium at 45 to 50°C, and the mixture was layered on the lower layer medium of a square petri dish to allow immobilization. (9)(8) was turned upside down and cultured at 35±1°C for about 16 to 24 hours, after which the number of plaques that appeared on the medium were counted and the number of phages per mL of the washout solution was calculated. The washout solution was sterilized by filtration.
[0089] (Evaluation of antiviral effect) Based on the above test results, the virus infectivity titer or the logarithmic reduction in the phage number was calculated as an index of the antiviral effect according to the following formula (1). R = Log(B / A) (1) R: logarithmic reduction in virus infectivity or phage count (antiviral effect) A: Viral infectivity or phage count after 24 hours exposure to the control (glass plate) B: Viral infectivity or phage count after 24 hours of exposure to test products (sections of nanodiamond particle-containing covers of each embodiment or comparative cover)
[0090] In the present specification, the antiviral effect was judged based on the following criteria: Evaluation A was judged as "sufficient antiviral effect", Evaluation B was judged as "has antiviral effect", and Evaluation C was judged as "no antiviral effect". A: Log reduction value is 2.0 or more (sufficient antiviral effect) B: Log reduction value is 1.0 or more but less than 2.0 (antiviral effect) C: Log reduction value is less than 1.0 (no antiviral effect)
[0091] In the "Test method for evaluating the suppression performance against viruses captured on a filter" of the JEM1467 "Household air purifier" (for bacteria and mold, refer to this standard), in all microbial tests, each microbial liquid is dropped onto the test product and immediately dried naturally before the start of the test, and the microbial liquid is allowed to act in a dried state for 24 hours, so the results obtained from this test are regarded as the antiviral (or antibacterial, antifungal) effect on a dry surface (in the gas phase).
[0092] (Method of measuring zeta potential) The zeta potential of the nanodiamond particles contained in the nanodiamond particle dispersion was measured by laser Doppler electrophoresis using a Malvern device (product name "Zetasizer Nano ZS"). When measuring the zeta potential, the nanodiamond particles contained in the nanodiamond particle dispersion were subjected to a dispersion treatment (e.g., ultrasonic treatment) so that the average particle diameter (D50) of the nanodiamond particles contained therein was 100 nm or less. The pH of the nanodiamond particle dispersion was also confirmed using pH test paper (product name "Three Band pH Test Paper", manufactured by AS ONE Corporation).
[0093] (Surface condition observation method) The surface of the above material was observed using a scanning electron microscope (SEM) (product name "SU5000") manufactured by Hitachi High-Tech Corp. The measurement conditions were accelerating voltage: 3.0 kV, spot intensity: 30, and conductive treatment: Pt.
[0094] (Method of calculating the amount of nanodiamond particles applied) The coating amount (A) of the nanodiamond particles per surface area of the material is calculated from the weight gain (X) and the surface area (Y) of the material as shown in the following formula (2). The weight gain (X) is calculated by subtracting the weight before coating from the weight after coating in the nanodiamond particle attachment process (here, the weight after coating refers to the weight after the material is dried after the coating process). The surface area (Y) of the material is calculated assuming that the surface is smooth. That is, for example, if the material is a rectangular flat plate, the area of the rectangle calculated by multiplying the short side of the rectangle by the long side corresponds to the surface area (Y) of the material. A=X / Y (2)
[0095] [Table 1]
[0096] From Table 1, it can be seen that the material of the present disclosure exhibits excellent antiviral effects against various viruses even on dry surfaces, which is the expected condition for the actual use of filters.
[0097] Variations of the invention according to the present disclosure are described below. [Appendix 1] A material comprising a main body having an uneven surface and nanodiamond particles attached to the uneven surface. [Appendix 2] The material described in Appendix 1, wherein the main body portion includes a substrate and a coating formed on the substrate. [Appendix 3] The material described in Appendix 2, wherein the coating is a zinc phosphate coating. [Appendix 4] The material described in claim 1 or 2, wherein the nanodiamond particles have a positive zeta potential. [Appendix 5] The material according to any one of appendices 1 to 4, having at least one effect selected from the group consisting of an antiviral effect, an antibacterial effect, and an antifungal effect. [Appendix 6] A material-attached filter, in which the material according to any one of appendices 1 to 5 is attached to the filter. [Appendix 7] A filter with the material described in appendix 6 for use in the gas phase. [Appendix 8] A nanodiamond particle dispersion liquid used for producing a material described in any one of Appendices 1 to 5, the nanodiamond particle dispersion liquid containing the nanodiamond particles and a solvent in which the nanodiamond particles are dispersed, the solvent containing at least water, and the concentration of the nanodiamond particles contained in the nanodiamond particle dispersion liquid being 0.01 to 10 mass%. [Appendix 9] At least one product selected from the group consisting of a coating liquid, a plating liquid, and a chemical conversion treatment liquid, comprising the nanodiamond particle dispersion liquid described in Appendix 8. [Explanation of symbols]
[0098] 1 Filter with material 2 Filter body 3 Materials 30 Purification Department 31 1st leg 32 Second leg 4. Main Unit 41 Base material 42 Membrane 42a Convex 42b Recess 5 Nano Diamond Particles
Claims
1. A material comprising a main body having a surface irregularity and nanodiamond particles attached to the surface irregularities.
2. The material of claim 1 , wherein the body portion comprises a substrate and a coating formed on the substrate.
3. The material of claim 2 , wherein the coating is a zinc phosphate coating.
4. 3. The material of claim 1 or 2, wherein the nanodiamond particles have a positive zeta potential.
5. The material according to claim 1 or 2, having at least one effect selected from the group consisting of an antiviral effect, an antibacterial effect, and an antifungal effect.
6. A filter with a material, comprising the material according to claim 1 or 2 attached to the filter.
7. A filter with the material according to claim 6, which is used in a gas phase.
8. A nanodiamond particle dispersion liquid used for producing the material according to claim 1 or 2, The nanodiamond particle dispersion liquid includes the nanodiamond particles and a solvent in which the nanodiamond particles are dispersed, The solvent contains at least water, A nanodiamond particle dispersion liquid, wherein the concentration of the nanodiamond particles contained in the nanodiamond particle dispersion liquid is 0.01 to 10 mass %.
9. At least one product selected from the group consisting of a coating liquid, a plating liquid, and a chemical conversion treatment liquid, comprising the nanodiamond particle dispersion liquid described in claim 8.
Citation Information
Patent Citations
Product for prevention of virus infection and use thereof
JP2022161727A
Nanodiamond-coated activated carbon
JP2022187457A
Protective mask, air filtration element and air treatment element
WO2021160178A1
Functional material and method for producing same
WO2021193843A1
Active filter layers, filter constructs and methods for improving a filter's capacity of capturing particles and neutralizing pathogenic particles
WO2022152974A1